Parametric yield curve modeling in an illiquid and undeveloped financial market - Davor Zoricic; Silvije Orsag (UTMS Journal of Economics, 2013)
This paper examines the possibility of applying two most popular parametric yield curve models (Nelson-Siegel and Svensson) in the Croatian financial market. In such an illiquid and undeveloped financial market yield curve modeling presents a special challenge primarily regarding the available market data. The use of the yield curve models is limited compared to the developed markets and the interpretation of the resulting yield curves requires much more cautiousness. However this paper clearly shows that the yield curve model is able to capture changes in the business cycle according to the macroeconomic theory and therefore provide valuable information to the financial industry and other economic subjects. It also suggests that the Svensson model which is an extension of the Nelson-Siegel model (and is therefore often preferred over the Nelson-Siegel model in the developed markets) suffers from overparameterization in the illiquid and undeveloped Croatian financial market.
Keywords: G12; E43; E44; 330; parametric yield curve models; illiquidity